Implementasi Kebijakan Sertifikasi Guru SMP Negeri Kota Payakumbuh - Rismasari, Roza; Hasan, Alizar (CV. ITTC INDONESIA, 2021)
Teacher Certification is an important program in improving the quality and qulity of National Education. Implementation in the key to the success of a program. Failure to implement the program means failure to achieve the objektives of the program.The focus of this study is to analyze the implementation of teacher certification policies at SMP Negeri Payakumbuh using interactive factors according to George C. Edward III’s ideas, namely communication, resources, disposition and bureaucratic structure thet play a role in policy implementation. The role of these four factors is very meaningful for policy implementation.This study uses a qualitative method through descriptive analysis with a case study model. The research subjects were Payakumbuh City Education Office employees, public junior high school principals, Payakumbuh public junior high school teachers. Data collection reachniques used are interviews and documentation.The result of this study indicate thet the implementation of teacher certification policies at SMP Negeri Payakumbuh has fulfilled four elements. Based on the role of the four elements thet determine the success of policy implementation, each element can be fulfilled even though it is not perfct. There are still many shortcomings in the elements of communication and bureaucratic structure. The delivery of the message makes the teacher confused about the actual program. Inconsistent SOPs, which change every year, make it difficult for teachers to adapt to the ever-new rules. The imperfecttions of the four elements did not hinder the process of implementing the policy for teacher certification at State Junior High Schools in Payakumbuh City.Interactive dialogue and discussion are alternative solusions that need to be considered. The ambiguity of the massage can be overcome by asking directly to the resource persons who master the material about teacher certification. And for the SOPs that are always changing, the regional (Payakumbuh City Education Office) should be able to convey the complaints and aspirations of teachers who are confused about the rule to the Provincial and Central Office because usually it is the policy maker who maka the SOPs so thet the policy can be implemented.